DETERMINATION OF THE COMPOSITION OF ASPHALT CONCRETE MIXTURES BASED ON EPOXY COMPONENTS FOR THEIR APPLICATION AS THIN-LAYER COATINGS OF ROAD BRIDGES - Onishchenko Arthur; Zelenovsky Vladimir (World Science, 2023)
This paper presents the results of the analysis of world and domestic experience, theoretical and practical research to assess the impact of thermosetting additives on the main indicators of bitumen and physical and mechanical properties of asphalt concrete. Ensuring increased track resistance, strength and crack resistance of pavements on road bridges today is one of the most important problems facing scientists and road workers in Ukraine. An urgent task is to improve the performance of these coatings in order to extend their service life and minimize the frequency of repair work, which, especially on bridges, cause great difficulties and require significant additional costs. There is no doubt that when using epoxy asphalt concrete as a thin-layer pavement, we get a strong, flexible surface, resistant to cracking and rutting. However, this is not yet a sufficiently researched material for its possible wide application, as it requires a special approach to the establishment of the composition and technology of its preparation. The application of a thin-layer coating on an orthotropic or reinforced concrete slab of the carriageway of the bridge made of epoxy asphalt-concrete mixture requires special attention in establishing the optimal selection of its composition and cooking technology. Particular attention should be paid to ensure the required viability of the epoxy asphalt mixture, the use of the desired hardener, which affects its properties, determining the required number of thermosetting modifiers, determining the duration of curing depending on temperature.